De Novo Donor-Specific HLA Antibodies Developing Early or Late after Transplant Are Associated with the Same Risk of Graft Damage and Loss in Nonsensitized Kidney Recipients. (6th March 2017) - Cioni, Michela; Nocera, Arcangelo; Innocente, Annalisa; Tagliamacco, Augusto; Trivelli, Antonella; Basso, Sabrina; Quartuccio, Giuseppe; Fontana, Iris; Magnasco, Alberto; Drago, Francesca; Gurrado, Antonella; Guido, Ilaria; et al.
Abstract : De novo posttransplant donor-specific HLA-antibody ( dn DSA) detection is now recognized as a tool to identify patients at risk for antibody-mediated rejection (AMR) and graft loss. It is still unclear whether the time interval from transplant to DSA occurrence influences graft damage. Utilizing sera collected longitudinally, we evaluated 114 consecutive primary pediatric kidney recipients grafted between 2002 and 2013 for dn DSA occurrence by Luminex platform. dn DSAs occurred in 39 patients at a median time of 24.6 months. In 15 patients, dn DSAs developed within 1 year ( early-onset group), while the other 24 seroconverted after the first posttransplant year ( late-onset group). The two groups were comparable when considering patient- and transplant-related factors, as well as DSA biological properties, including C1q and C3d complement-binding ability. Only recipient age at transplant significantly differed in the two cohorts, with younger patients showing earlier dn DSA development. Late AMR was diagnosed in 47% of the early group and in 58% of the late group. Graft loss occurred in 3/15 (20%) and 4/24 (17%) patients in early- and late-onset groups, respectively (p = ns). In our pediatric kidney recipients, dn DSAs predict AMR and graft loss irrespective of the time elapsed between transplantation and antibody occurrence.